Modulation of innate immunity in airway epithelium for host-directed therapy - Myszor, Iwona T.; Gudmundsson, Gudmundur Hrafn (Frontiers in Immunology, 2023)
Innate immunity of the mucosal surfaces provides the first line defense from invading pathogens and pollutants conferring protection from the external environment. Innate immune system of the airway epithelium consists of several components including mucus layer, mucociliary clearance of beating cilia, production of host defense peptides, epithelial barrier integrity provided by tight and adherens junctions, pathogen recognition receptors, receptors for chemokines and cytokines, production of reactive oxygen species and autophagy. Therefore, multiple components interplay with each other for efficient protection from pathogens that still can subvert host innate immune defenses. Hence, modulation of innate immune responses with different inducers to boost host endogenous front-line defenses in the lung epithelium to fend off pathogens and to enhance epithelial innate immune responses in the immunocompromised individuals is of interest for host directed therapy. Herein, we reviewed possibilities of modulation innate immune responses in airway epithelium for host directed therapy presenting an alternative approach to standard antibiotics.